Fractalkine Elicits Chemotactic, Phenotypic, and Functional Effects on CX3CR1+ CD272 NK Cells in Obesity-Associated Cancer - Lysaght, Joanne; Conroy, Melissa (My University, 2021)
Esophagogastric adenocarcinomas (EAC) are obesity-associated malignancies underpinned by severe immune dysregulation and inflammation. Our previous work indicates that NK cells migrate to EAC omentum, where they undergo phenotypic and functional alterations and apoptosis. In this study, we investigate whether such erroneous chemotaxis to omentum is paralleled by compromised NK cell infiltration of EAC patient tumor and examine the role of the inflammatory chemokine fractalkine in shaping the NK cell mediated response. Our data show diminished NK cell frequencies in EAC tumor compared with those in the circulation and reveal that intratumoral NK cell frequencies decline as visceral obesity increases in EAC patients. Our in vitro findings demonstrate that antagonism of fractalkine receptor CX3CR1 significantly reduces NK cell migration to EAC patient derived, omental adipose tissue conditioned media, but not toward tumor-conditioned media. These data suggest fractalkine is a key driver of NK cell chemotaxis to omentum but has a lesser role in NK cell homing to tumor in EAC. We propose that this may offer a novel therapeutic strategy to limit NK cell depletion in the omentum of obese EAC patients, and our data suggest the optimal timing for CX3CR1 antagonism is after neoadjuvant chemoradiotherapy. Our functional studies demonstrate that fractalkine induces the conversion from CX3CR1+ CD272 to CX3CR12CD27+ NK cells and increases their IFNg and TNF-a production, indicative of its role in shaping the dominant NK cell phenotype in EAC omentum. This study uncovers crucial and potentially druggable pathways underpinning NK cell dysfunction in obesity-associated cancer and provides compelling insights into fractalkine’s diverse biological functions
PUBLISHED
Keywords: Cancer; Inclusive Society; Biomedical sciences; CANCER; Tumour immunology and immunotherapy